STUDI AWAL KOMPOSISI DAN DINAMIKA VEGETASI POHON HUTAN GUNUNG POHEN CAGAR ALAM BATUKAHU BALI - Sutomo Sutomo; N. K. Erosi Undaharta; T. M. Bangun; I.N. Lugrayasa (Environmental Research Center (PPLH) of Udayana University, 2012)
A permanent 1 ha (100 m × 100 m) plot with 25 subplots (quadrates) and 5 level rows ofaltitudinal difference was established for long-term monitoring of plant diversity and dynamicsin a tropical mountain forest of Pohen Mountain, Batukahu Nature Reserve, Bali, Indonesia.Enumeration of all tree species > 10 cm DBH (diameter at breast height) yielded a total of notless than 300 individuals that belonged to 24 species and 19 families with Podocarpaceae wasthe most abundant family in the forest. Plant density varied from 10-20 individuals/quadrates(20 m × 20 m). Species composition and diversity varied between each quadrates in a rowwithin the 1 ha plot. Third row (intermediate altitude) exhibits the highest species diversitywhereas the fifth row (the highest altitude) had the lowest species diversity. Ordinationanalysis showed that species composition in the first, second and third rows are differentwith species composition in the fourth and fifth row. Most of the pioneer tree species exhibitedclumped distribution over the plot. This study provides baseline information for themanagement and restoration on the tropical mountain forests of Pohen Mountain, BatukahuNature Reserve post wildfire in 1994.